The Prevalence of Depression in Patients undergoing Haemodialysis (Journal of Nobel Medical College, 2024)
Background: End-stage renal disease requires dialysis treatment, with haemodialysis and peritoneal dialysis being the two primary modalities. These treatments often lead to psychological distress, including depression and anxiety, which adversely affect patients' quality of life and treatment adherence. Although both dialysis modalities have been associated with mental health issues, limited research compares the prevalence of depression and anxiety between haemodialysis and peritoneal dialysis patients.Materials and Methods: This observational cross-sectional study, conducted at Nobel Medical College Teaching Hospital, Biratnagar, enrolled 129 dialysis patients. Ethical approval was obtained, and informed consent was acquired from participants. The beck depression inventory, beck anxiety inventory, and the hospital anxiety and depression scale were used to assess depression and anxiety levels. Data were analyzed using the Student’s t-test and chi-square tests, with a significance level set at p < 0.05.Results: Of the 129 patients, 27.27% of haemodialysis patients and 42.10% of peritoneal dialysis patients exhibited depression on the beck depression inventory. On the hospital anxiety and depression, 10.90% of haemodialysis patients and 21.05% of peritoneal dialysis patients showed depression symptoms. Anxiety was observed in 27.27% of haemodialysis patients and 10.52% of peritoneal dialysis patients according to the Beck Anxiety Inventory. The differences between groups were not statistically significant (p > 0.05).Conclusion: Depression and anxiety are prevalent among dialysis patients, with no significant difference in the prevalence rate between haemodialysis and peritoneal dialysis groups. This highlights the need for routine screening for mental health disorders in dialysis patients to improve their overall well-being. Tailored mental health interventions should be developed to address the psychological needs of dialysis patients.